Violence towards health care workers in a Public Health Care Facility in Italy: a repeated cross-sectional study - Magnavita Nicola; Heponiemi Tarja (BMC, 2012)
Abstract Background Violence at work is one of the major concerns in health care activities. The aim of this study was to identify the prevalence of physical and non-physical violence in a general health care facility in Italy and to assess the relationship between violence and psychosocial factors, thereby providing a basis for appropriate intervention. Methods All health care workers from a public health care facility were invited to complete a questionnaire containing questions on workplace violence. Three questionnaire-based cross-sectional surveys were conducted. The response rate was 75 % in 2005, 71 % in 2007, and 94 % in 2009. The 2009 questionnaire contained the VIF (Violent Incident Form) for reporting violent incidents, the DCS (demand/control/support) model for job strain, the Colquitt 20 item questionnaire for perceived organizational justice, and the GHQ-12 General Health Questionnaire for the assessment of mental health. Results One out of ten workers reported physical assault, and one out of three exposure to non-physical violence in the workplace in the previous year. Nurses and physicians were the most exposed occupational categories, whereas the psychiatric and emergency departments were the services at greatest risk of violence. Workers exposed to non-physical violence were subject to high job strain, low support, low perceived organizational justice, and high psychological distress. Conclusion Our study shows that health care workers in an Italian local health care facility are exposed to violence. Workplace violence was associated with high demand and psychological disorders, while job control, social support and organizational justice were protective factors.